Factors Affecting Total Cholesterol Level in the Pre-Elderly and Elderly in Kedaung Village - Aisyah, Yonita Laty; Ilmi, Ibnu Malkan Bakhrul; Marjan, Avliya Quratul (Jurnal Kesmas Jambi, 2025)
The prevalence of hypercholesterolemia in Indonesia is recorded in the elderly group at 15.5%. Pre-elderly and elderly are at-risk groups who are prone to hypercholesterolemia, especially in several conditions, such as over-nutrition status, high fat and low fiber food intake, and having a family history of hypercholesterolemia. This study aims to analyze the factors that influence total cholesterol levels in pre-elderly and elderly people in Kedaung Village. The study was conducted analytically observational with a cross-sectional design. Respondents in this study were 50 pre-elderly and elderly obtained from sample calculations using stratified sampling techniques. Data collection was taken using an SQ-FFQ questionnaire and analyzed by univariate analysis showed the frequency distribution of respondents' characteristics, and bivariate analysis was conducted using a chi-square test to identify the relationship between variables. The results of the study reported that 56% of respondents with total cholesterol levels ≥200 mg/dL. A total of 70% of respondents consumed high fat intake, 58% of respondents consumed low fiber intake, 60% of respondents had overweight status, and 64% had a family history of hypercholesterolemia. Analysis showed that the determinant factors associated with respondents' total cholesterol levels were fat intake (p=0.035), fiber intake (p=0.013), and family history (p=0.015). Pre-elderly and elderly with total cholesterol levels ≥200 mg/dL were found in respondents with high fat intake, low fiber intake, and a family history of hypercholesterolemia.